Effect of explosive characteristics on the explosive welding of stainless steel to carbon steel in cylindrical configuration - Mendes, R. (2013)
The aim of this research is to study the influence of explosive characteristics on the weld interfaces of stainless steel AISI 304L to low alloy steel 51CrV4 in a cylindrical configuration. The effect of ammonium nitrate-based emulsion, sensitized with different quantities and types of sensitizing agents (hollow glass microballoons or expanded polystyrene spheres) and Ammonium Nitrate Fuel Oil (ANFO) explosives on the interface characteristics is analyzed. Research showed that the type of explosive and the type and proportion of explosive sensitizers affect the main welding parameters, particularly collision point velocity. The morphology of the wavy weld interfaces, chiefly the amplitude and length of the waves, is affected both by the impact velocity and the type and particle size of the explosive sensitizers, and increases with particle size. All the weld interfaces, except welds done with ANFO, displayed localized melted and solidified regions, whose chemical composition resulted from the contribution of both flyer and base metal.